Pure White Cell Aplasia and Necrotizing Myositis - Peter Geon Kim; Joome Suh; Max W. Adelman; Kwadwo Oduro; Erik Williams; Andrew M. Brunner; David J. Kuter (Case Reports in Hematology)
Pure white cell aplasia (PWCA) is a rare hematologic disorder characterized by the absence of neutrophil lineages in the bone marrow with intact megakaryopoiesis and erythropoiesis. PWCA has been associated with autoimmune, drug-induced, and viral exposures. Here, we report a case of a 74-year-old female who presented with severe proximal weakness without pain and was found to have PWCA with nonspecific inflammatory necrotizing myositis and acute liver injury on biopsies. These findings were associated with a recent course of azithromycin and her daily use of a statin. Myositis improved on prednisone but PWCA persisted. With intravenous immunoglobulin and granulocyte-colony stimulating factor therapies, her symptoms and neutrophil counts improved and were sustained for months.